(3EOGQI GdYdGbGJ GdYGeI (B:s (3GdeONd GdESJQGJjLj (B/s - (3GdLeGd, QGSe eMeOs; (3YjGOs ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 2005)
(3hab GdcJGH Gdi MO HYjO aj Gf jLeY dbGQFg GZdH TJGJ eG jge GdYdGbGJ GdYGeI h GOGQJgG ef efXhQ GSJQGJjLjs
Keywords: (3GdGJUGd s; (3GdeONd GdESJQJjLjs; (3GdYdGbGJ GdYGeIs